Do the Entrepreneurship Education and the Entrepreneurship Motivation Have a Relationship with the Gender? A Quantitative Study from Indonesia - Tutik Inayati (Research Synergy Foundation, 2021)
The increasing number of entrepreneurship programs, formal or nonformal, intends to increase the number of entrepreneurs in Indonesia. However, the number of entrepreneurs may not be associated with whether a person had been enrolling in entrepreneurship education. This study analyzes the association between entrepreneurial education and entrepreneurial motivation. Furthermore, we also want to investigate whether the two variables mentioned above have a correlation with gender. Of 101 collected respondents, the results are generated using the Chi-square independence test for data analysis. We found no association between gender and entrepreneurial motivation, no association between entrepreneurial education and entrepreneurial motivation, and no association between gender and entrepreneurial education. Thus, entrepreneurial motivation is fundamentally subjective and does not consider gender. This result generates significant recommendations for the Indonesian government to improve entrepreneurial activities and motivation in the future.